VARIATION IN TEMPERATURE OF SURFACE WATER MASSES OF THE OCEAN DURING THE OLIGOCENE - Nikolayev S.D.; Blyum N.S.; Nikolayev V.I. (My University, 1987)
The paper reports on a study whose results indicate that the Oligocene ocean was colder than the present-day ocean in this latitude belt. But this does not mean that the global mean temperature in the Oligocene was lower than in the present epoch. The mean annual surface temperatures in the surface zone of the ocean (0 to 250 m) during the later Oligocene, calculated for the more oceanic Southern Hemisphere in the zone between 0° and 30° S, differed by 5.4° from the present-day temperatures; by 1.9 in the 0 to 50° S zone, and by only 0.04 in the 0 to 60° S zone. Thus, the global mean temperatures in the Oligocene were equal to or even somewhat higher than the present-day temperatures, and the temperature changes that we have identified are due to the fact that the thermal field had a different configuration from at present. Overall, the surface and subsurface waters of the Oligocene ocean were colder than at present in the lower latitudes and considerably warmer in the higher latitudes. In contrast to the present-day temperature distribution, the thermal field of the oceans in the Northern and Southern Hemispheres was relatively symmetrical in the Oligocene.
Keywords: Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен